The Students Learning from Home Experiences during Covid-19 School Closures Policy In Indonesia - Purniadi Putra; Fahrina Yustiasari Liriwati; Tasdin Tahrim; Syafrudin Syafrudin; Aslan Aslan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article analyzed the learning experience of students at home during the school closing period in response to the Covid-19 pandemic in Indonesia. Through this study, an in-depth understanding of the life experiences, perceptions, and motivation of students were obtained from either the school or their parents. These outputs would be input into policy making and solving learning problems towards a new normal era. Now the school closures have been running for almost seven months and it almost about to reopening this mid-August 2020. To understand this phenomenon issue, some data searching have been performed ranging from daily papers, academic journal, and educational related literature. The data search then analyzed under the phenomenological application approach. Compiling the existing data and students voices, this study showed that the students learning experiences during six month learning from home responding the national policy stopping the corona virus spreading can be reported based on 10 websites visited have expressed their best coverage over students learning difficulty and challenge from different perspectives. Most websites mentioned students hardship in learning from home caused the lack of learning resources such not access to internet and parents ability to support their children learning. Keywords: School Closures Policy In Covid-19, Covid-19, Learning Online